2019
DOI: 10.1097/ajp.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Postoperative Analgesic Effect of Dexmedetomidine or Dexamethasone Added to Lidocaine Through Infraclavicular Block in Forearm Surgery

Abstract: Objective: The objective of this study was to compare the analgesic efficacy of dexamethasone versus dexmedetomidine added to lidocaine using infraclavicular block in patients undergoing forearm fracture surgery. Method: Seventy-five patients aged 20 to 60 years were recruited for a prospective, double-blinded, randomized clinical trial. Ultrasound-guided infraclavicular brachial plexus block was performed in 3 groups by injecting 28 mL lidocaine plus 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…A total of 396 articles were retrieved from the preliminary search. After screening, 7 articles [14][15][16][17][18][19][20] were finally included for analysis, with 465 patients.…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
“…A total of 396 articles were retrieved from the preliminary search. After screening, 7 articles [14][15][16][17][18][19][20] were finally included for analysis, with 465 patients.…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
“…Of the 286 trials identified from the literature search strategy and other sources, 57 RCTs [ 20 – 23 , 34 86 ] met the inclusion criteria, representing a total of 3332 patients. Among the 286 articles, 90 duplicate articles were excluded initially.…”
Section: Resultsmentioning
confidence: 99%
“…Across all included studies, a total of 3332 patients were assessed. DEX was used as an adjuvant to several different local anesthetics, which included ropivacaine [ 23 , 34 , 39 , 41 , 42 , 45 47 , 49 , 50 , 52 , 56 , 57 , 59 , 63 66 , 68 , 72 – 74 , 76 , 78 , 80 , 81 , 84 , 85 ], bupivacaine [ 20 , 35 , 37 , 38 , 40 , 51 , 53 55 , 67 , 69 , 71 ], levobupivacaine [ 21 , 43 , 44 , 48 , 60 62 , 79 , 83 ], and lidocaine [ 22 , 36 , 70 , 77 , 86 ]. Across the studies, the dose of DEX ranged from 0.5 μg/kg to a total of 150 μg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Several adjuncts have been investigated to elevate the analgesic response of lidocaine for infraclavicular block. 7 …”
Section: Introductionmentioning
confidence: 99%